MODERN TENDENCIES IN THE ORGANIZATION AND MANAGEMENT OF FINANCE OF SMALL BUSINESS ENTERPRISES (World Economics and Finance Bulletin, 2023)
The article examines modern trends in the organization and management of finance of small business enterprises. It can be observed that the role and importance of small business enterprises in the country's economy is increasing. Sources of financing of small business enterprises were also discussed
Keywords: Small business enterprises; diversification